ANALISIS MODEL LOGIT KUMULATIF UNTUK MENENTUKAN DETERMINAN USIA KAWIN PERTAMA WANITA DI KABUPATEN BALANGAN - Aulia Syifa Annisa; Dewi Sri Susanti (RAGAM: Journal of Statistics & Its Application, 2023)
The Province of South Kalimantan is one of the five provinces in Indonesia with the highest teenage marriage rate from 2017 to 2020.  Based on 13 South Kalimantan regencies/cities, it is known that Balangan Regency has the greatest percentage of women's age at first marriage under 19 years compared to other regencies/cities, which is 55.58%. The purpose of this study is to identify the factors that influence women's age at first marriage in Balangan Regency in 2020. In this investigation, ordinal logistic regression with the cumulative logit model was used.  The findings revealed that the highest education ever/currently obtained by a woman (X1), parents' age at first marriage (X2), the highest diploma of the head of the household (X3), employment status of the head of the family (X4), location of place of residence (X5), poverty status (X6), and migration (X7) had no significant effect.  Furthermore, using the Spearman rank correlation coefficient, it was discovered that the highest education ever/currently obtained by a woman  (X1) has a substantial correlation/closeness of link with women's age at first marriage by 28%.  Women with a higher degree of education are less likely to marry at a young age, whereas women with a lower level of education are more likely.